Design of Management Information System Serikat Karyawan on PT TELKOM DIVRE V East Java - Prasetyo, Mochamad Yudi; Nurcahyawati, Vivine; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Serikat Karyawan (SEKAR) Telkom is a democratic, independent, accountable, open and non-political organization to any organization. SEKAR Telkom consists of almost all Telkom employees. The purpose of SEKAR Telkom is to provide protection, defense of both rights and interests and improve the welfare of Telkom's employees and their families. In achieving these objectives, SEKAR Telkom has several business activities such as Human Resource Activity monitoring, Employee Complaint Handling, Dewan Pimpinan Daerah (DPD) Activities and Financial Management. But in the implementation of each business activity, there are problems of information exchange to support business activities of SEKAR Telkom still using conventional ways that impact data transparency to members are not met. The solution of these problems is to create a structured Information System that can meet the information needs of any existing business activities within SEKAR Telkom organization. Based on the results of the implementation of Serikat Karyawan Management Information Units generated that can help organizations SEKAR Telkom to achieve its goals by providing media information exchange in accordance with business activities SEKAR Telkom organization.